A prospective randomized double blind placebo controlled crossover study of fluoxetine efficacy in the prophylaxis of chronic daily headache in children and adolescents Estudo randomizado prospectivo duplo-cego cruzado controlado com placebo da eficácia da fluoxetina na profilaxia da cefaléia crônica diária na infância e adolescência - José Luiz Dias Gherpelli; Sandro Blasi Esposito (Arquivos de Neuro-Psiquiatria)
Thirty-two children (21 female and 11 male), between 7 and 14 years old, with chronic daily headache (CDH) were consecutively included in a prospective, randomized, double blind, placebo controlled crossover study. The patients were divided in group I (fluoxetine vs. placebo), with 17 patients and group II (placebo vs. fluoxetine), with 15 patients. After one month of baseline headache frequency recording, the patients received fluoxetine in dosages from 0.25 to 0.50 mg/kg for three months. A wash out period of one month was followed by another three months treatment period. Results showed a significant decrease in headache frequency in the study period [78% reduction in group I (p<0.025), and 45% reduction in group II (p=0.025)]. Gastrointestinal adverse effects were observed in nine patients (29%) that received fluoxetine, compared with 3 (10%), with placebo. We conclude that fluoxetine efficacy is not higher than placebo in the prophylaxis of CDH in children and adolescents. Trinta e duas crianças (21 feminino, 11 masculino), com idades entre 7 e 14 anos, com cefaléia crônica diária (CCD) foram incluídos consecutivamente no estudo prospectivo, randomizado, duplo-cego, cruzado com placebo. Os pacientes foram divididos em grupo I (fluoxetina vs. placebo), com 17 pacientes, e grupo II (placebo vs. fluoxetina) , com 15 pacientes. Após um mês de registro da freqüência da cefaléia, os pacientes receberam fluoxetina em doses de 0,25-0,5 mg/kg por três meses. Após período de interrupção da droga de um mês, seguiu-se novo período de três meses de tratamento. Os resultados mostraram diminuição estatisticamente significativa da freqüência da cefaléia [78% de redução no grupo I (p<0,025) e 45% de redução no grupo II (p<0,025)]. Efeitos colaterais gastrointestinais ocorreram em 9 pacientes (29%) na vigência da fluoxetina, comparado com 3 (10%) com placebo. Concluímos que não houve diferença entre o efeito da fluoxetina e do placebo na profilaxia da CCD em crianças e adolescentes.